A Safe-by-Design Approach for the Synthesis of a Novel Cross-Linked Hyaluronic Acid with Improved Biological and Physical Properties - Sabrina Sciabica; Riccardo Barbari; Riccardo Fontana; Giovanni Tafuro; Alessandra Semenzato; Daniela Traini; Dina M. Silva; Larissa Gomes Dos Reis; Luisa Canilli; Massimo Terno; Peggy Marconi; Anna Baldisserotto; et al. (MDPI AG, 2023)
Hyaluronic acid (HA) is a polymer with unique biological properties that has gained in interest over the years, with applications in pharmaceutical, cosmetic, and biomedical fields; however, its widespread use has been limited by its short half-life. Therefore, a new cross-linked hyaluronic acid was designed and characterized using a natural and safe cross-linking agent, such as arginine methyl ester, which provided improved resistance to enzymatic action, as compared to the corresponding linear polymer. The antibacterial profile of the new derivative was shown to be effective against S. aureus and P. acnes, making it a promising candidate for use in cosmetic formulations and skin applications. Its effect on S. pneumoniae, combined with its excellent tolerability profile on lung cells, also makes this new product suitable for applications involving the respiratory tract.